Critical linkages between quality management practices and performance from Indian IT enabled service SMEs. (7th June 2018) - Basu, Rana; Bhola, Prabha; Ghosh, Indranil; Dan, Pranab K
Abstract : The purpose of this paper is to critically investigate the relationship among quality management (QM) practices with their direct and indirect effects on performance outcome by means of conceptual extension and generalisation. The paper uses factor analysis and structural equation modelling which has been tested using cross-sectional data collected from IT enabled small and medium service firms in India. The analysis shows the interdependency of QM practices and the importance of a systematic approach for managing QM practices. The findings from this study indicate that the nature of the interrelationships between these core QM practices is unique to the Indian context. The unique contribution of this study has been in terms of its model-building approach towards designing a linkage model showing interdependencies among critical QM practices with its direct and indirect effects on performance outcome. Such a holistic framework with plausible interaction effects has not been studied earlier in the Indian context with sector-specific relevance to IT enabled service SMEs. Further the paper recommends suggestions for improvement along with managerial implications and future scope of study.